The longue durée of short-lived infrastructure – Roads and state authority in South Sudan. Issue 133 (July 2022) - Bachmann, Jan; Ruth Pendle, Naomi; Moro, Leben
Abstract: Drawing on the literature on the temporalities of infrastructure, this article focuses on the cyclical assertion of centralized authority through road-building in South Sudan, where roads are repeatedly built, projects paused, roads ruined, and then rebuilt again. The landscapes of South Sudan are littered with the decaying infrastructure projects of previous governments and political visions, seemingly pointing to a past of failed futures and the limits of government power. At the same time, the recurrent proclamations of temporary power through infrastructure have come to embody a form of permanent order in itself. We specifically focus on two types of internationally-funded roads built around the country's independence in 2011: the 'oil' road between Bentiu and Rumbek as well as the 'stabilization roads' in Warrap and Lake States. Initially, these roads displayed the promissory capacity of the new government to reorient politics and the economy to the new Juba-based centre of power. However, they quickly deteriorated. Still, the lack of permanence of the roads did not necessarily undermine the power of the government. In South Sudan, centralized authority is not only built through the road's completion, but through its unending incompletion that allows both the endless presence of new road projects as much as the entrenchment of coercive forms of managing (dis-)order in the country's infrastructural frontier. At the same time, people living along the roads often incorporated the short-livedness of the roads into their own visions of the future and more local political orientations.